Establishing an exemplary Islamic society (in Turkey): an analysis of Bediuzzaman Said Nursi's reform - Ushama, Thameem (Hamdard Foundation, 2018)
The author provides a brief profile of Said Nursi (1877-1960) contributions to Islamic thought and specifically a content analysis of his Risale-i Nur (Risa.lah-i Nur) to explore his methods with regard to a moderate articulation of the Qur'an's message. The paper also discusses Nursi's method of problem solving through an academic discourse that integrates revealed and acquired knowledge. This method strengthens faith and unity by identifying social and intellectual maladies and providing remedies. Nursi's Risa.le-i Nur focuses on an exegesis that targets individual training, family reform and the gestalt cultivation of a Muslim society. Contemporary challenges are addressed vis-a-vis dangers presented by Western imperialism as well as anti-Islamic dynamics, including Orientalism. We then introduce Nursi's educational reforms, which stressed a more proper integration of scientific and religious instruction with a view towards modern technology and political struggles. Finally, we review his emphasis on compassion and the importance of sincerity, in addition to the role of the Sunnah and the elimination of doubt in believing hearts.